Analysis of the Influence of Domestic Investment (PMDN), Foreign Investment (PMA), Government Expenditure, and Minimum Wages on Regional Original Income (PAD) in Regencies and Cities in West Nusa Tenggara Province 2015-2023 - Simorangkir, Elysa Suciati; Firmansyah, M.; Hidayat, Ali Akbar (Westscience Press, 2025)
This study aims to determine the Effect of Domestic Investment, Foreign Investment, Government Expenditure, and Minimum Wages on Regional Original Income (PAD) in Regencies and Cities of West Nusa Tenggara Province in 2015-2023. This study is a quantitative study with an associative approach. This study uses secondary data obtained from the Central Statistics Agency (BPS), the Regional Financial and Asset Management Agency (BPKAD), and the Investment and One-Stop Integrated Service Office (DPMPTSP). The method used in this study is panel data analysis using Eviews 12. The results of the study show that Domestic Investment has a positive but insignificant effect. On the other hand, Foreign Investment has a negative but significant effect. While Government Expenditure and Minimum Wages have a positive and significant effect. Simultaneously, Domestic Investment, Foreign Investment, Government Expenditure and Minimum Wages have a positive and significant effect on Regional Original Income in Regencies and Cities in West Nusa Tenggara Province.